Bortezomib as a treatment option in patients with Waldenström macroglobulinemia - Dimopoulos, M.A.; Chen, C.; Kastritis, E.; Gavriatopoulou, M.; Treon, S.P. (Clinical Lymphoma, Myeloma and Leukemia, 2010)
Waldenström macroglobulinemia (WM) is a B-Cell lymphoproliferative disorder characterized by lymphoplasmacytic bone marrow infiltration and immunoglobulin M (IgM) monoclonal gammopathy. It remains incurable, with a median survival of 5-10 years in symptomatic WM. Current first-line treatment options include alkylating agents, nucleoside analogues, and rituximab-based therapies. However, primary or secondary resistance invariably develops. Thus, new treatment options are needed. Preclinical studies have shown that the proteasome inhibitor bortezomib targets signaling pathways of relevance in WM. Bortezomib, alone and in combination with rituximab, has demonstrated notable activity in clinical studies in patients with WM, predominantly in phase II trials in the relapsed or refractory setting. In newly diagnosed patients, bortezomib plus rituximab and dexamethasone is highly active (complete response/near-complete response = 22%). Bortezomib-based therapies result in rapid responses, potentially making them suitable treatment options for patients with hyperviscosity-related symptoms who require a rapid reduction in IgM level. In addition, bortezomib appears unique in reducing rituximab-associated IgM flares. Bortezomib is generally well tolerated in WM. However, neurotoxicity is common and might be the cause of dose reduction or treatment discontinuation. Bortezomib has no adverse effect on stem cell harvesting and engraftment, making it a feasible treatment option in transplantation-eligible patients. These encouraging data have led to the inclusion of bortezomib as a salvage treatment option in the recently updated Fourth International Workshop on Waldenstrom's Macroglobulinemia treatment recommendations.
Keywords: IgM flares; Immunoglobulin M; M's macroglobulinemia; Nuclear factor-KB; Waldenströ